Exploring the effectiveness of sustainability measurement: which ESG metrics will survive COVID-19? - Atkins, Jill (Journal of business ethics, 2023)
This paper aims to investigate the current state of play on Environmental Social and Governance (ESG) integration and check the validity of the current metrics system by assessing if it will survive the COVID-19 crisis. By adopting a qualitative research approach through semi-structured anonymous interviews with 14 senior managers of six European listed companies we use a framework by assessing the mechanisms of reactivity on the effectiveness of ESG measures in times of COVID-19. By interpreting the practitioners’ points of view through the lens of the sociological framework by Espeland and Sauder (Am J Sociol 113:1-40, 2007) our findings show different mechanisms of reactivity by companies on the effectiveness of ESG measures in times of COVID-19, i.e., active and passive conformity and active resistance. We also identified the main Corporate Social Responsibility (CSR) institutional factors that affect managers’ reactivity. An extensive re-formulation of the ESG metrics is required in the light of times of crisis, given that accountability and transparency are strongly linked to quantitative measures which can play a critical role in the financial system and investors’ engagement. Particularly, the strict distinction between "E", "S" and "G" issues should be abandoned claiming a different holistic re-design of sustainability measures by considering the increasing relevance of the Social dimension in time of COVID-19. This study provides a valuable contribution to the existing literature on the measurement of sustainability within the link of accountability and crisis by highlighting new corporate needs to re-design the ESG metrics system.